2002
DOI: 10.1143/jjap.41.5226
|View full text |Cite
|
Sign up to set email alerts
|

Laser Short-Pulse Heating of Gold–Copper Two-Layer Assembly: Thermo-Elasto-Plastic Analysis

Abstract: Nuclei moving through magnetized materials at high velocities are subject to very intense transient magnetic fields, resulting from the ion-solid interaction in the polarized material. The transient field has been used for g-factor measurements of short-lived nuclear states for more than a decade. Still the origin of the field is not fully explained. The present paper presents a detailed discussion of the inherent assumptions of a model based on polarized bound electrons (PBE). The contact fields from unpaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…However, owing to the short time (of the order of 10 212 s), experimental measurements of stress could not be carried out. Since the use of the FEM code (ANSYS) in the stress simulations is well established and the predictions are almost in qualitative agreement with the previous results [19,29,30], the authors are satisfied with the accuracy of the predictions. The stability criterion is assured when selecting the time and space increments in the computer program [30].…”
Section: Calculation Procedures For Stressessupporting
confidence: 70%
See 1 more Smart Citation
“…However, owing to the short time (of the order of 10 212 s), experimental measurements of stress could not be carried out. Since the use of the FEM code (ANSYS) in the stress simulations is well established and the predictions are almost in qualitative agreement with the previous results [19,29,30], the authors are satisfied with the accuracy of the predictions. The stability criterion is assured when selecting the time and space increments in the computer program [30].…”
Section: Calculation Procedures For Stressessupporting
confidence: 70%
“…Yilbas [12] introduced an electron kinetic theory approach to model the laser heating process. Later, the model was extended to include three-dimensional effects, multilayer structures, and phase change processes [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A more rigorous approach would have consisted in accounting for the thermal resistance at the Au/Ag interface and the difference in the electron–phonon (e–ph) coupling constants, heat capacities, and thermal conductivities of the two metals, which would have induced a discontinuity in the thermal dynamics at the boundary. [ 45 ] However, for the case of a Au/Ag interface, it has been shown by Yilbas [ 46 ] that the short‐pulse induced dynamics of both T e and T l are smooth (i.e., without discontinuities at the interface). Therefore, the influence of the Au/Ag thermal resistance is negligible.…”
Section: Ultrafast Transient Optical Responsementioning
confidence: 99%
“…He indicated that non-equilibrium heating had significant effects on laser-induced thermo-mechanical phenomena. Yilbas [14][15][16][17][18], Yilbas and Shuja [19], and Yilbas and Arif [20] studied the laser short-pulse heating process and predicted temperature rise, entropy generation rate, and thermo-mechanical responses in metallic materials.…”
Section: Introductionmentioning
confidence: 99%